Produção textual e multimodalidade: uma proposta com realidade aumentada - Kelling, Vera Lúcia Vargas de Souza (2015)
The technological revolution experienced by contemporary society and the advancement of media tools point to the need to integrate education in this context , aligning their actions with these materials. Therefore, it is necessary for teachers to appropriate technological knowledge and to use these tools in their educational practices. In this context, it is the teaching of Portuguese Language, whose main topics are the reading and textual production. In this perspective , this work presents a proposal of textual multimodal production with the use of Augmented Reality technology aiming to motivate the reading activities and text production as well to improve this educational process. To development this work was used the methodology of action research and qualitative analysis, using a questionnaire and semi-structured interviews as data collection instrument. It was considered that the use of technology to support the classroom textual production enabled new strategies for this activity, which motivated and encouraged the participation of students in school activities. This research indicated that the use of AR enhances the production of multimodal texts, because this technology allows the inclusion of images, 3D objects and audio in the texts produced by the students and was considered as an important tool of motivation to reading and writing. The results analyzed in this dissertation indicate that the students showed a expressive learning in the textual productions through AR technology. Finally, it is emphasized that the use of this technology in activities of multimodal texts production constitutes an important approach that can be used by teachers who want to insert the technology into their practices of textual production.